Recent Trends for The Development of the “Tax System” and its Impact on Improvement “Tax Revenues” in Iraq - Lateef, Abdulameer Zamil; kadhim, Fadhil abbas; AL-Jassam, Noor Nadhim Hameed (South Asian Journal of Social Sciences and Humanities, 2022)
The objective of the study is to decide the correct methods through which the "Tax system" may  be advanced in a way this is well matched with numerous environmental variations and trends, in  addition to displaying the position of the "Tax system" in improving "Tax Revenues" and  encouraging financing the state's budget. The research is based on two fundamental assumptions:  (1) the development of the "Tax system" allows to enhance tax revenue and finance the state's  budget. The sample of research is of personnel inside the General Tax Authority, which include  administrators, accountants, and auditors, for the fiscal year finishing December 31, 2019.  Analytical equipment was used to attain the studies outcomes, which showed that the tax branch  has a susceptible hobby in transferring towards appropriate and cutting-edge techniques that It is  feasible to reduce tax evasion, as study has concluded that there is a set of appropriate scientific  methods that can help in decreasing tax evasion, improving tax sales, and financing the country's  budget.
Keywords: Tax system; Tax Revenues; Iraq